Designing a Rubric for the Summative Evaluation of Students’ Translation at University Level - S. Mohammed , Shadiya S. Mohammed; M. H. A. Al-Rubai’I , Alya’ (Academic Journal of Nawroz University, 2024)
This quantitative and qualitative study aims to determine the extent to which translation teachers accept the proposed criteria for evaluating their students’ translation according to academic rank and the differences between translation teachers’ viewpoints on the proposed criteria according to years of experience for the purpose of designing a rubric for the summative evaluation of students’ translation at the university level. The study addresses the following questions: To what extent the university translation teachers accept the proposed criteria for the summative evaluation rubric according to academic rank? Do the translation teachers view the proposed criteria for the summative evaluation rubric distinctly according to teaching experience? Eight translation teachers completed the Pilot Study questionnaire, and 45 translation teachers received the Main Study questionnaire. The data were statistically analysed to test the study’s validity and reliability. The study found out that the reliability and validity were generally acceptable; translation teachers’ acceptance of the suggested criteria varied. However, there were no appreciable discrepancies in their opinions about the criteria based on the latter variables. The most important conclusions were as follows: Translation teachers’ approval of the suggested criteria for evaluating their students’ translation varies according to academic rank and years of experience in teaching. No significant discrepancies in the translation teachers’ perspectives on their application of the proposed criteria according to academic rank and years of experience in teaching. Summative evaluation of translation can be effectively accomplished using a rubric including criteria for Equivalence, Translation Method, Mechanics of Writing, Naturalness, and Readability.